Impact of First-Year Coursework on College Students’ Academic Motivation, Use of Learning Strategies, and Understanding of Liberal Education - Armenta, Armando; Earle, Sofia; Sobottka, Edward; Bica, Lori A. (My University, 2019)
Seminars for new first-year college students first appeared in the U.S. around 1910 and were a common staple for several decades. In the late 1930s, faculty began to question the academic value of these courses, and they had nearly disappeared from campuses by the mid-1960s. The resurgence in new-student seminars began in the early 1970s, and by the 1980s, the seminars had become common once again. Despite the longstanding history of the first-year seminar, research about its effectiveness was very limited until the late 1980s. Today, much of the available research dates from the 1990s, with the pace of published studies slowing down after 2000. It is imperative for campuses that offer first-year seminars to investigate the efficacy of these courses on a regular basis for the purposes of enhancing student learning and making wise decisions about resource allocations. The purpose of current study is to assess the effectiveness of a new First Year Experience course, IDIS 155: Exploring Liberal Education. Intended to develop students’ understanding of Liberal Education (LE), the course also aims to promote learning strategies for success in college.
Color poster with text and images.
Keywords: First-year seminars; College students; Motivation; Interdisciplinary approach to education; Posters